Do Internal Household Factors Affect Poverty Status? Evidence From Indonesia - Pardomuan Sihombing; Ade Marsinta Arsani (Junal Ilmu Manajemen, 2020)
Many factors affect poverty status. The purpose of this paper is to assess the determinants of poverty status in Indonesia, especially for internal household factors. By employing binary logistic regression using poverty status as the dependent variable, this study finds that internal household factors are significantly affecting poverty status in Indonesia. However, due to Yogyakarta's socio-economics characteristics, some findings are different from several previous studies. This study finds that age, education, and employment sectors of household heads and their spouse affect poverty status significantly. Gender, as well as the number of children and household size, also have a significant impact on poverty status in Indonesia. The implication of this result encourages investment not only for the household head but also for their spouse, as well as for all household members, enhance women's capability to get a better job and reduce dependency ratio.